Climate change and corporate financial performance - Lian Liu; John Beirne; Dina Azhgaliyeva; Dil Bahadur Rahut (Asian Development Bank Institute (ADBI), 2024)
Climate change impacts will continue to worsen with rising greenhouse gas (GHG) emissions and global temperatures, underscoring the growing necessity to foresee and comprehend the impact of climate change risks on economic activity. Using quarterly firm-level data of 173 firms from the People's Republic of China (PRC) over the period Q1 2018-Q2 2022, this study estimates the impact of firms' exposure to climate-related risks on their financial performance. The results indicate a notable adverse effect of climate change exposure on firms' rate of return, with a lag of around two years. Firms located in more climate-vulnerable coastal areas and high-income provinces experience relatively greater negative impacts on their financial returns. Our findings have important policy implications for firms aiming to maximize their returns through enhanced climate change mitigation and adaptation efforts.
Keywords: Q56; F61; Q54; 330; climate change; climate change exposure; corporate financial performance; PRC